2019
DOI: 10.21873/anticanres.13792
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Mineralocorticoid Receptor Expression Predicts Dismal Local Relapse-free Survival in Non-triple-negative Breast Cancer

Abstract: Background/Aim: The aim of the study was to investigate the prognostic role of androgen receptor (AR), mineralocorticoid receptor (MR) and glucocorticoid receptor β (GRβ) expression in HER-2 negative breast cancer patients. Materials and Methods: The study population (n=152) was enriched with triple-negative breast cancers (TNBC) (n=96; 63.2%). The median follow-up time was 100 months. AR, MR and GRβ immunocytochemical staining was compared with that of epithelial-mesenchymal transition (EMT) markers (vimentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…However, some investigators have explored the MR’s potential role in both cancers. Both glucocorticoids and mineralocorticoids, together with PR, can decrease BCa cell proliferation ( Leo et al 2004 ), and a high cytoplasmic expression of MR has been associated with a poor survival of ER+/PR+/HER2- BCa patients ( Jääskeläinen et al 2019 ). In PCa, abiraterone treatment can result in excess of aldosterone and its precursors, which increases the risk for hypertension and cardiovascular diseases ( Pia et al 2013 , Narayanan et al 2016 ).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…However, some investigators have explored the MR’s potential role in both cancers. Both glucocorticoids and mineralocorticoids, together with PR, can decrease BCa cell proliferation ( Leo et al 2004 ), and a high cytoplasmic expression of MR has been associated with a poor survival of ER+/PR+/HER2- BCa patients ( Jääskeläinen et al 2019 ). In PCa, abiraterone treatment can result in excess of aldosterone and its precursors, which increases the risk for hypertension and cardiovascular diseases ( Pia et al 2013 , Narayanan et al 2016 ).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Several isoforms of GR have been described to this day: GRα (the ‘standard’ form), GRβ—Which is present in the nucleus (however, some studies revealed its significant presence only in the cytoplasm [ 175 ]), has no LBD [ 169 ], exhibits constant activity and suppresses the effects of GRα. Apart from that, GRβ possesses other specific DNA targets and is responsible for glucocorticoid resistance.…”
Section: Glucocorticoid Receptormentioning
confidence: 99%
“…In turn, GRα is repressed by Akt1, which phosphorylates its S134 residue [ 170 ] GRβ is preferentially expressed with AR in breast tumors and was revealed to be present in 92.1% of specimens, typically in triple-negative tumors. It has been shown that its presence is correlated with less vimentin expression in breast tumors in general and in non-triple-negative breast cancers and with lesser proliferation in breast cancers in general [ 175 ].…”
Section: Glucocorticoid Receptormentioning
confidence: 99%
See 2 more Smart Citations